Attitudes of Students at the Faculty of Education, University of Ljubljana, Towards Slovenian as the Language of Instruction - Skubic Darija (University of Maribor Press, 2013)
The paper discusses the Slovenian language as the language of instruction inhigher education context. First, the status of Slovenian throughout history isbriefly described. Second, the author points out the role of the Slovenian standardlanguage in the educational system from kindergarten to the university, and the fullfunctional role of the Slovenian language within higher education, i.e. Slovenianas the academic language in different disciplines. Further, the paper provides anoutline of language guidelines as included in various documents, such as TheCountry Profile of Slovenia (2003), The National Programme for Language Policy(2007-2011), The White Paper (2011), The Common European Framework forLanguages (2001), and the draft of the National Programme for Language Policy2012-2016. The empirical part focuses on a survey, which investigated into theattitudes of students at the Faculty of Education towards Slovenian as the languageof instruction. The conclusions drawn from the survey suggest some strategies forimproving the current language practice in the higher education context.